2001
DOI: 10.1002/1522-2683()22:6<1086::aid-elps1086>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A two primers random amplified polymorphic DNA procedure to obtain polymerase chain reaction fingerprints of bacterial species

Abstract: Polymerase chain reation (PCR) fingerprints are used to characterize and recognize bacteria and are generally obtained using universal primers that generate an array of DNA amplicons, which can be separated by electrophoresis. Universal primers 8F and 1491 R have been used to amplify specifically 16S rDNA. We have used these primers at an annealing temperature of 50 degrees C. Agarose gel electrophoresis of PCR products revealed several bands. The band pattern of each bacterial species was different and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 20 publications
1
29
0
12
Order By: Relevance
“…It had some more differences with the protein pattern of O. tritici LMG 18957 T TP-RAPD patterns. In a previous study we showed that TP-RAPD patterns allow the differentiation among rhizobial species (39) and that, within a species, the TP-RAPD pattern is identical for different strains. Figure 9 shows the TP-RAPD patterns of the strains isolated in the present study compared to those of O. anthropi and O. tritici.…”
Section: Downloaded Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…It had some more differences with the protein pattern of O. tritici LMG 18957 T TP-RAPD patterns. In a previous study we showed that TP-RAPD patterns allow the differentiation among rhizobial species (39) and that, within a species, the TP-RAPD pattern is identical for different strains. Figure 9 shows the TP-RAPD patterns of the strains isolated in the present study compared to those of O. anthropi and O. tritici.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…GTTTGATCCTGGCTCAG-3Ј, Escherichia coli positions 8 to 27) and 1522R (5Ј-GGTTACCTTGTTACGACTT-3Ј, E. coli positions 1509 to 1491) were used at 2 M final concentration (39). PCR conditions were as follows: preheating at 95°C for 9 min; followed by 35 cycles of denaturing at 95°C for 1 min, annealing at 45°C for 1 min, and extension at 72°C for 2 min; with a final extension at 72°C for 7 min.…”
Section: Isolation From Plant Nodules Strains Lup21mentioning
confidence: 90%
“…DNA extraction was carried out as described previously (Rivas et al, 2001). PCR amplification of 16S rDNA was carried out using primers 59-AGAGTTTGATCTGGCTCAG-39 and 59-AAGGAGGTGATCCANCCRCA-39 under conditions described previously (Velázquez et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that bacterial strains that show identical patterns in TP-RAPD analysis belong to the same species, whereas different species have distinct patterns (Rivas et al, 2001). In the present study, strain CCBAU 25048 T , S. granuli JCM 13254 T , S. zoogloeoides JCM 20728 T , Rhizobium etli CFN 42 T , Rhizobium leguminosarum USDA 2370 T , Ensifer meliloti USDA 1002 T and Mesorhizobium loti NZP 2213 T were incubated in YMA medium (Vincent, 1970) at 28 u C. DNA extracted from these strains with the method of Terefework et al (2001) was used in TP-RAPD analysis as described previously (Trujillo et al, 2005).…”
mentioning
confidence: 99%